IMPLEMENTASI PEMBELAJARAN KITAB KUNING MELALUI METODE AL-HASRI WAL QOSRI DALAM MENINGKATKAN PEMAHAMAN SANTRI DI PONDOK PESANTREN AT-TAROQQI KARONGAN SAMPANG - Ach. Fatoni (Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study examines the implementation of kitab kuning (classical Islamic texts) instruction through the Al-Hasri wal Qosri method at Pondok Pesantren At-Taroqqi Karongan, Sampang, and its impact on improving students’ comprehension. The research employed a descriptive qualitative approach with a case-study design. Data were collected through participant observation, in-depth interviews with the pesantren leader, education administrators, teachers, students, and students’ parents/guardians, as well as documentation review. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, with credibility ensured through source, method, and theoretical triangulation. The findings indicate that: (1) students’ understanding developed gradually from the ability to read unvowelled texts (without harakat) to the ability to analyze grammatical structures and contextualize the content of the texts, with mastery of nahwu and sharaf serving as the foundational basis; (2) the Al-Hasri wal Qosri method was implemented systematically through stages of preparation, intensive instructional delivery, and continuous written–oral evaluation, enabling students to learn in a more structured and efficient manner; and (3) key supporting factors included a clear instructional structure, teachers’ commitment and competence, and the pesantren learning ecosystem, while obstacles stemmed from differences in students’ backgrounds and motivation, variations in teacher quality, a dense curriculum, the dominance of Arabic technical terms, and a learning culture that remains relatively passive. The study recommends differentiated instruction, strengthened contextualization strategies, and pedagogical training for teachers to optimize the implementation of the method.